Theoretical and method trends guiding community psychology based HIV research and implications for marginalised groups. - Shirley, Amy (My University, 2012)
This study explores how international and South African community psychology has studied HIV in the past twenty years, emphasising the methodological and theoretical aspects of research being produced. Concurrently, this study situates itself within an empowerment theory framework and has sought to comment upon marginalised groups and their presence in published community psychology-based HIV research. The research made use of data generated from a content analysis of selected journal articles from the South African Journal of Psychology, the American Journal of Community Psychology, the Journal of Community Psychology, and the Journal of Community and Applied Social Psychology over the period 1990-2009. The results reflect a dearth of community psychology research concerning HIV and a reliance on positivistic methodologies across contexts, as well as a predominant focus on epistemologies relating to risk and prevention. It was found that whilst interest in marginalised groups within community psychology based HIV research has increased particularly in the last decade, the voices of some of the most vulnerable groups remain relatively silent. It is understood that a move away from more traditional health psychology methods and understandings of HIV, to a more critical conceptualisation is imperative for the field of community psychology with regards to this prominent social problem.
Keywords: Community psychology; HIV research; South Africa; Marginalised groups; Publication trends; Empowerment theory